2021
DOI: 10.3389/fmicb.2021.666052
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Genomic Sampling Refines Current Understanding of the Distribution and Evolution of Sulfur Metabolisms in the Desulfobulbales

Abstract: The reconstruction of modern and paleo-sulfur cycling relies on understanding the long-term relative contribution of its main actors; these include microbial sulfate reduction (MSR) and microbial sulfur disproportionation (MSD). However, a unifying theory is lacking for how MSR and MSD, with the same enzyme machinery and intimately linked evolutionary histories, perform two drastically different metabolisms. Here, we aim at shedding some light on the distribution, diversity, and evolutionary histories of MSR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 95 publications
(163 reference statements)
0
19
0
Order By: Relevance
“…It has been reported that Desulfobacterota and Campilobacterota are composed of sulfate-reducing bacteria and sulfide-oxidizing bacteria respectively. 51,52 Their variations might be related to sulfate groups contained in PYP. Previous studies have also shown that sulfate groups have a positive effect on the ability of natural plant polysaccharides to ameliorate metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Desulfobacterota and Campilobacterota are composed of sulfate-reducing bacteria and sulfide-oxidizing bacteria respectively. 51,52 Their variations might be related to sulfate groups contained in PYP. Previous studies have also shown that sulfate groups have a positive effect on the ability of natural plant polysaccharides to ameliorate metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Desulfobacterota and Campilobacterota showed changes in gut microbiota in the PYP group compared with those in the HS group. It has been reported that Desulfobacterota and Campilobacterota are composed of sulfate‐reducing bacteria and sulfide‐oxidizing bacteria respectively 51,52 . Their variations might be related to sulfate groups contained in PYP.…”
Section: Discussionmentioning
confidence: 99%
“…The genes and pathways present in the genome are consistent with the ability of strain RS19-109 T to reduce sulfate with hydrogen, disproportionate thiosulfate, reduce iron, reduce nitrate, and utilize bicarbonate/CO 2 as a carbon source. To date, genomic markers for S 0 disproportionation have not been identified (Slobodkin & Slobodkina, 2019; Ward et al ., 2021), and we were thus unable to ascribe any genes or pathways to the ability of RS19-109 T to disproportionate S 0 .…”
Section: Methodsmentioning
confidence: 99%
“…Given the significant limitations and uncertainties presented by the geochemical record, pairing geochemical analysis with top-down phylogenetics approaches can provide a novel perspective into the emergence and spread of distinct sulfur-cycling microbial metabolisms on the early Earth. Though no dedicated molecular clock work to date has been conducted on sulfur metabolisms, genomics-based studies suggest that dissimilatory sulfite and sulfate reduction and sulfide oxidation emerged as early forms of energy metabolism (25)(26)(27)(28). Phylogenetics analysis suggests that the dsr genes, which catalyze the reduction of sulfite to sulfide or in the reverse for sulfide oxidation, were among the first sulfur-based genes to arise (25,27), with the reductive form arising first (29).…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic anoxygenic photosynthesizers would likely have emerged soon thereafter, possibly using these genes to oxidize sulfur and sulfide ( 30, 31 ). Genomics analyses also indicate that sulfur disproportionation likely arose subsequently ( 27, 28 ). As the oceans became increasingly oxygenated, thiosulfate would have become more available, paving the way for the evolution of thiosulfate oxidation/reduction via the sox pathway ( 26 ).…”
Section: Introductionmentioning
confidence: 99%